Defense spending and income inequality: evidence from selected Asian countries - Mohd Tahir, Hirnissa; Habibullah, Muzafar Shah; Abdul Hamid, Baharom (Canadian Center of Science and Education, 2009)
This paper examines the causality between defense spending and income inequality in selected Asian countries namely Malaysia, Indonesia, Singapore, Philippines, India and South Korea for the period 1970-2005. Autoregressive Distributed Lag (ARDL) bounds testing procedure is employed to (1) analyze the impact of defense spending on income inequality and (2) the impact of income inequality on defense spending as well. Interestingly our results indicate one way causality running from defense spending to income inequality only for the case of Malaysia and bidirectional causality for the case of Singapore. As for the remaining countries, no meaningful relationship could be detected and it can be seen as sign of good governance in these countries.